Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Sure, let's rewrite the given equation [tex]\( y = \frac{1}{6}x - 1 \)[/tex] in the form [tex]\( Ax + By = C \)[/tex] using integer coefficients for [tex]\( A \)[/tex], [tex]\( B \)[/tex], and [tex]\( C \)[/tex].
1. Start with the given equation:
[tex]\[ y = \frac{1}{6}x - 1 \][/tex]
2. To eliminate the fraction, multiply every term by 6:
[tex]\[ 6y = x - 6 \][/tex]
3. Rearrange the terms to achieve the desired form [tex]\( Ax + By = C \)[/tex]:
- Subtract [tex]\( x \)[/tex] from both sides to bring [tex]\( x \)[/tex] to the left-hand side:
[tex]\[ 6y - x = -6 \][/tex]
- For standard form, it's conventional to write the [tex]\( x \)[/tex]-term first. We have:
[tex]\[ -x + 6y = -6 \][/tex]
However, it's more standard (and often preferable) to have the coefficient of the [tex]\( x \)[/tex]-term positive. Therefore, multiply through by -1:
[tex]\[ x - 6y = 6 \][/tex]
So, the equation [tex]\( y = \frac{1}{6}x - 1 \)[/tex] in the form [tex]\( Ax + By = C \)[/tex] with integer coefficients is:
[tex]\[ x - 6y = 6 \][/tex]
Where:
- [tex]\( A = 1 \)[/tex]
- [tex]\( B = -6 \)[/tex]
- [tex]\( C = 6 \)[/tex]
Thus, rewritten, it is:
[tex]\[ x - 6y = 6 \][/tex]
1. Start with the given equation:
[tex]\[ y = \frac{1}{6}x - 1 \][/tex]
2. To eliminate the fraction, multiply every term by 6:
[tex]\[ 6y = x - 6 \][/tex]
3. Rearrange the terms to achieve the desired form [tex]\( Ax + By = C \)[/tex]:
- Subtract [tex]\( x \)[/tex] from both sides to bring [tex]\( x \)[/tex] to the left-hand side:
[tex]\[ 6y - x = -6 \][/tex]
- For standard form, it's conventional to write the [tex]\( x \)[/tex]-term first. We have:
[tex]\[ -x + 6y = -6 \][/tex]
However, it's more standard (and often preferable) to have the coefficient of the [tex]\( x \)[/tex]-term positive. Therefore, multiply through by -1:
[tex]\[ x - 6y = 6 \][/tex]
So, the equation [tex]\( y = \frac{1}{6}x - 1 \)[/tex] in the form [tex]\( Ax + By = C \)[/tex] with integer coefficients is:
[tex]\[ x - 6y = 6 \][/tex]
Where:
- [tex]\( A = 1 \)[/tex]
- [tex]\( B = -6 \)[/tex]
- [tex]\( C = 6 \)[/tex]
Thus, rewritten, it is:
[tex]\[ x - 6y = 6 \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.